(3cTa GdZeG aj CNHGQ GdMeGs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3bGd GdTjN LdGd GdOjf GdSjhWi gPG LRA ai CNHGQ GdMeG SejJg cTa GdZeG Yf CHj gQjQI QVi Gddg Yfg s
(3BNQgG (B:s
(3hHOgf GdhQO fGaY hPdc CSad GdbOejf hEPG Ogf UGMH MeG GdQHY HTMe GdJeSGM ScfJ Yfg hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg fbhd ddTjN OGhO ai NhGU fHGJjI heYOfjI hMjhGfjI JajO ai GdMeis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs